DETERMINATION OF HEAT EXCHANGE ON THE INTERNAL SIDE OF PIPELINES IN DISTRICT HEATING SYSTEMS (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
The present article deals with the heat exchange on the internal side of the pipelines during the distribution of heat through heat networks as the heat exchange parameters must be known for the purpose of calculating the heat loss within the distribution of heat through heat networks. The calculations and outcomes published in the article were carried out for above-ground heat networks, for the nominal diameter DN125 at the temperature of the environment of -15 °C which represents, according to STN EN 12831 - 1 standard, the design outdoor temperature in the town of Košice. The calculation was also extended to all nominal diameters used in secondary pipelines of the distribution network.